REVIEW OF METHODS AND RESULTS OF EXPERIMENTAL INVESTIGATIONS OF STEEL AND STEEL CONCRETE STRUCTURES UNDER SPECIAL IMPACT - Alekseytsev, A.V.; Kurchenko, N.S. (Stroitelʹnaâ mehanika inženernyh konstrukcij i sooruženij (Online), 2018)
The modern experimental studies review of the resistance of the most common steel and steel-concrete building structures in emergency conditions is performed. The main directions of experimental design are revealed under certain types of special influences that affect the mechanical safety of structures. An overview of the experimental studies of steel and steelconcrete lamellar-structural elements survivability in local damage to columns, described in the modern scientific literature is presented. Tests of lamellar and light steel thin-walled structures on the effect of cyclic loading are described. Data on the limit static loads of beams and spatial frame systems are given. Attention to testing of structures for combined impact and explosive effects is paid. Photos and diagrams of laboratory samples and objects are given. As a result of the review, a conclusion is made about the prospects for further studies of the survivability of steel structures under emergency actions. It is noted, that now there is a need to expand the nomenclature of standardized types of emergency actions. That will allow to more effectively carrying out a complex of preventive measures that let us to increase the mechanical safety of structures and minimize potential risks of material and social losses in the event of emergencies.